2011
DOI: 10.1016/j.limno.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of brine discharge to rivers and streams: Methodology of rapid impact assessment

Abstract: a b s t r a c tInduced by a brine discharge study for a submerse gas storage cavern project, a suitable methodology for rapid impact assessment had to be found. In this paper a simple stochastic, stationary model is described for assessment of intensity and temporal variability of chloride pollution at the regional scale of the rivershed. Chloride concentration is used as a proxy of salinity. It is assumed to be the result of deterministic process (flow-dependent) and stochastic variation (estimated for bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…These findings align with those of previous studies, which reported that biological quality of salt polluted streams can be affected by conductivities as low as 1.5 mS cm -1 (Dunlop et al, 2005;Hart et al, 1991;Horrigan et al, 2005;Kefford et al, 2011), or even lower (Cormier et al, 2013;Kefford et al, 2011). Anyhow, the damage to the aquatic invertebrate community can be expected to increase with increasing conductivity (Berezina, 2003;Böhme, 2011;Braukmann and Böhme, 2011;Cañedo-Argüelles et al, 2012;Hart et al, 1991;Horrigan et al, 2005;Pinder et al, 2005;Piscart, 2005;Williams et al, 1999). It is important to notice the reduction in EPT taxa at sites P3 and P4, and IMMi-L, Iberian Mediterranean Multimetric Index, using qualitative data (Munné and Prat, 2009); IMMi-T, Iberian Mediterranean Multimetric Index, using quantitative data (Munné and Prat, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…These findings align with those of previous studies, which reported that biological quality of salt polluted streams can be affected by conductivities as low as 1.5 mS cm -1 (Dunlop et al, 2005;Hart et al, 1991;Horrigan et al, 2005;Kefford et al, 2011), or even lower (Cormier et al, 2013;Kefford et al, 2011). Anyhow, the damage to the aquatic invertebrate community can be expected to increase with increasing conductivity (Berezina, 2003;Böhme, 2011;Braukmann and Böhme, 2011;Cañedo-Argüelles et al, 2012;Hart et al, 1991;Horrigan et al, 2005;Pinder et al, 2005;Piscart, 2005;Williams et al, 1999). It is important to notice the reduction in EPT taxa at sites P3 and P4, and IMMi-L, Iberian Mediterranean Multimetric Index, using qualitative data (Munné and Prat, 2009); IMMi-T, Iberian Mediterranean Multimetric Index, using quantitative data (Munné and Prat, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…The maximum conductivity value in soil observed in the effects phase was 1628 mS cm 21 , and freshwater bodies are not supposed to be affected by salt leaching up to 1000 mS cm 21 . Nevertheless, negative effects on less tolerant aquatic communities have previously been observed [58][59][60][61], with a change in the community structure (substitution of the less tolerant taxa to more tolerant) [62,63].…”
Section: (B) Effects Of Salinization On Coastal Ecosystemsmentioning
confidence: 99%
“…Climate change is altering the biogeochemical cycles on the planet and shifting water temperature, pH, dissolved oxygen concentration, and salinity . In fact, direct relationships between anthropogenic CO 2 release and alterations in the water cycle, which result in salinity variations, have been already established. Other direct human activities, such as irrigation, , industrialization and agricultural expansion, effluent disposal, , or dam management, are also behind these salinity variations. These changes and their effects can be even more important in transitional waterbodies, such as estuaries, deltas, or coastal lagoons, which constitute less than 5% of the brackish areas worldwide but provide about half of the global fish catch …”
Section: Introductionmentioning
confidence: 99%